Pathophysiology and therapeutic potential of cardiac fibrosis - Hironori Hara; Norifumi Takeda; Issei Komuro (BMC, 2017)
Abstract Inflammatory and fibrotic responses to myocardial damage are essential for cardiac repair; however, these responses often result in extensive fibrotic remodeling with impaired systolic function. Recent reports have suggested that such acute phase responses provide a favorable environment for endogenous cardiac regeneration, which is mainly driven by the division of pre-existing cardiomyocytes (CMs). Existing CMs in mammals can re-acquire proliferative activity after substantial cardiac damage, and elements other than CMs in the physiological and/or pathological environment, such as hypoxia, angiogenesis, and the polarity of infiltrating macrophages, have been reported to regulate replication. Cardiac fibroblasts comprise the largest cell population in terms of cell number in the myocardium, and they play crucial roles in the proliferation and protection of CMs. The in vivo direct reprogramming of functional CMs has been investigated in cardiac regeneration. Currently, growth factors, transcription factors, microRNAs, and small molecules promoting the regeneration and protection of these CMs have also been actively researched. Here, we summarize and discuss current studies on the relationship between cardiac inflammation and fibrosis, and cardiac regeneration and protection, which would be useful for the development of therapeutic strategies to treat and prevent advanced heart failure.